Ethanolic extract from leaves of Bixa orellana L.: A potential natural food preservative (2012)
This paper reports the minimum inhibitory concentration (MIC) of ethanolic extract from leaves of Bixa orellana L. against bacteria and fungi of interest in the food industry, such as Escherichia coli, Bacillus cereus, Pseudomonas aeruginosa, Staphylococcus aureus, Salmonella typhimurium, Shigella sonnei, Listeria monocytogenes, Candida albicans, Saccharomyces cerevisiae, Aspergillus niger, Penicillium chrysogenum and Byssochlamys fulva. In addition, the antioxidant activity of the ethanolic extract was determined by evaluating their scavenging of the DPPH radical. The ethanolic extract exhibited a broad spectrum of antimicrobial activity for both Gram positive and Gram negative bacteria with MICs of 256-1024ppm. For MICs between 1 and 512ppm, fungi showed greater sensitivity to extract than bacteria. Nisin used as positive control caused growth inhibition of all bacteria tested, with MICs between 2 and 1024ppm. In contrast, fungi were not inhibited by nisin. Results also indicated that the ethanolic extract had good scavenging of DPPH radical with an EC 50 of 7710 ±0.6318ppm.